Risk of herpes zoster and family history: A Meta-analysis of case-control studies - Yi Chun Lai; Yik Weng Yew (Wolters Kluwer Medknow Publications, 2016)
Background: Herpes zoster (HZ) results from the reactivation of latent varicella zoster virus (VZV) residing in dorsal root and cranial nerve ganglia. Advanced age and dysfunctional cell-mediated immune responses are well-established risk factors for VZV reactivation. There have been recent interests in whether there is an increased risk of the disease associated with a positive family history. Aims and Objectives: We aimed to conduct a meta-analysis to evaluate the association between HZ infection and family history. In addition, we investigated the dose-response relationship between HZ infection and the number of relatives with a history of HZ. Materials and Methods: Observational studies were searched from MEDLINE, EMBASE, and Cochrane Central Register from inception to April 15, 2015. The Meta-analysis of Observational Studies in Epidemiology guidelines were followed in conducting this study. To estimate the pooled odds ratio, random-effects model of DerSimonian and Laird was used. Heterogeneity between studies was assessed using the I2 statistic. A dose-response meta-analysis with studies that reported appropriate data were done using the generalized least squares for trend method. Results: Five studies, yielding a total of 4169 subjects, were identified for meta-analysis. Cases with HZ were 3.03 (95% confidence interval [CI]: 1.86-4.94, P < 0.001) and 3.27 (95% CI: 1.75-6.10, P < 0.001) times more likely to report the first-degree relatives and total relatives with a history of HZ, respectively. A significant positive dose-response relationship between the risk of HZ infection and the number of relatives with a history of HZ was also demonstrated (P < 0.001). Conclusions: This meta-analysis demonstrated that family history is a significant risk factor for HZ infection. This risk has a dose-response relationship with the number of relatives with a history of HZ.